Navigating digital publics for playful production: A cross-case analysis of two interest-driven online communities - Ksenia A. Korobkova; Matthew Rafalow (Digital Culture & Education, 2016)
This article argues that the set of skills and strategies associated with managing digital publics online represent an emergent literacy practice of importance to literacy researchers and educators. Drawing on two case studies of online communities popular with contemporary youth to learn, play, and socialize, we articulate how youth participants strategically negotiate multiple audiences online with varying levels of publicity in order to achieve learning outcomes. In one case, players of a popular production-centered video game share their content in ways that garner the specific kind of audience and feedback they need for their projects. In another, members of an online fan fiction community analyze and negotiate expectations of their audience in order to craft media that garners attention and sustains readership. Both examples identify how skills centered on navigating and managing publics – that is, multiple audiences that are permeable across a wider public online – constitute a recognizable and important “new literacy” in digitally mediated learning environments. We situate our empirical studies in sociocultural theories of learning and historicize the work in contemporary digital cultures and the general move from the writer-reader relationship to writer-audience relationships to more complex relationships within digital publics. The article ends with considerations for literacy researchers, policymakers, and practitioners interested in technology-mediated practices of today’s youth.